1999
DOI: 10.1016/s0022-510x(99)00044-1
|View full text |Cite
|
Sign up to set email alerts
|

Sleep-disordered breathing at an early stage of amyotrophic lateral sclerosis

Abstract: Eighteen amyotrophic lateral sclerosis (ALS) patients having neither respiratory complaints nor subjective symptoms of sleep disturbance were studied by using an ambulatory multi-parameter monitoring system during sleep. They were divided into two groups: 11 patients with predominantly bulbar form and seven with non-bulbar form. After performing daytime pulmonary function tests, the presence of sleep-disordered breathing (SDB) was evaluated by using a portable device. ALS patients did not show significant SDB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
4

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(58 citation statements)
references
References 18 publications
2
51
0
4
Order By: Relevance
“…[4][5][6][7] In the presence of diaphragmatic dysfunction, REM sleep decreases. 8 Furthermore, sleep disturbances and nocturnal desaturations have been observed in ALS patients with normal respiratory function and preserved diaphragmatic innervation.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7] In the presence of diaphragmatic dysfunction, REM sleep decreases. 8 Furthermore, sleep disturbances and nocturnal desaturations have been observed in ALS patients with normal respiratory function and preserved diaphragmatic innervation.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6] The 2009 American Academy of Neurology Practice Parameter on ALS treatment recommended the use of NIV for patients demonstrating evidence of respiratory compromise. 7 A recent Cochrane Review also evaluated the effects of night-time mechanical ventilation in patients with neuromuscular or chest wall disorders, including patients with ALS.…”
Section: S C I E N T I F I C I N V E S T I G a T I O N Smentioning
confidence: 99%
“…with bulbar involvement [3], diaphragmatic involvement [1] or in the presence [2] or absence [50] of respiratory and/or sleep-related symptoms. In the largest unselected cross-sectional study, GAY et al [4] reported a mean AHI of 11.3 events?h -1 in 21 subjects, of whom seven had an AHI w10.…”
Section: Amyotrophic Lateral Sclerosismentioning
confidence: 99%
“…However, the principal cause of nocturnal desaturation was hypoventilation. Comparing the PSG results of the various studies, the frequency of sleepdisordered breathing is very variable (16.7-76.5%), and appears to reflect the prevalence of respiratory and sleep-related symptoms, and to a lesser extent, the impairment of daytime respiratory function in the populations studied [2][3][4][5]50]. A similar variation is seen with the degree of disruption of sleep architecture [1,[3][4][5].…”
Section: Amyotrophic Lateral Sclerosismentioning
confidence: 99%